2016
DOI: 10.1021/acsnano.6b02231
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle Reprograms Pancreatic Tumor Microenvironment and Inhibits Tumor Growth

Abstract: Altered tumor microenvironment (TME) arising from a bidirectional crosstalk between the pancreatic cancer cells (PCCs) and the pancreatic stellate cells (PSCs) is implicated in the dismal prognosis in pancreatic ductal adenocarcinoma (PDAC), yet effective strategies to disrupt the crosstalk is lacking. Here, we demonstrate that gold nanoparticles (AuNPs) inhibit proliferation and migration of both PCCs and PSCs by disrupting the bidirectional communication via alteration of the cell secretome. Analyzing the ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
159
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(174 citation statements)
references
References 80 publications
8
159
0
1
Order By: Relevance
“…For example, AuNPs (20 nm diameter) were found to reduce proliferation in PSCs and PCCs significantly but not in normal human pancreatic ductal epithelial cells or nonmalignant NIH3T3 fibroblasts. 6 These observations are in good agreement with previous findings that AuNPs do not modulate the proliferation of normal ovarian epithelial cells 10,11 and do not induce systemic toxicity following 3–4 weeks of repeated injections. 10,11 This reduction in proliferation was determined to result, at least in part, from suppression of mitogen-activated protein kinase (MAPK) signaling, which mediates growth-factor-induced proliferation.…”
supporting
confidence: 92%
See 4 more Smart Citations
“…For example, AuNPs (20 nm diameter) were found to reduce proliferation in PSCs and PCCs significantly but not in normal human pancreatic ductal epithelial cells or nonmalignant NIH3T3 fibroblasts. 6 These observations are in good agreement with previous findings that AuNPs do not modulate the proliferation of normal ovarian epithelial cells 10,11 and do not induce systemic toxicity following 3–4 weeks of repeated injections. 10,11 This reduction in proliferation was determined to result, at least in part, from suppression of mitogen-activated protein kinase (MAPK) signaling, which mediates growth-factor-induced proliferation.…”
supporting
confidence: 92%
“…), the current research has identified exciting novel properties of AuNPs as stand-alone cancer therapeutics for PDAC. 6 These results are particularly interesting because AuNPs were demonstrated to exert this therapeutic behavior specifically within populations of cancer cells but not nonmalignant cells. For example, AuNPs (20 nm diameter) were found to reduce proliferation in PSCs and PCCs significantly but not in normal human pancreatic ductal epithelial cells or nonmalignant NIH3T3 fibroblasts.…”
mentioning
confidence: 98%
See 3 more Smart Citations